DAMPAK INTERAKSI ANTARA KEBIJAKAN UTANG DAN KEBIJAKAN DIVIDEN DALAM MENILAI PERUSAHAAN - Meythi Meythi (University of Merdeka Malang, 2012)
This research aimed to examine and know empirical evidence of the positive effect of debt policy on firms valuewith dividend policy as moderating variable. Samples used in this research were manufacturing companieslisted in Indonesia Stock Exchange in 4 years observation period (2007-2010). Total samples were 13 companies.The data were collected by using purposive sampling method. The result of moderated regression analysis(MRA) showed that debt policy did not effect firms value with dividend policy as moderating variable. Thus,the hypothesis of the research was not empirically supported.